Evaluation of the Performance of the Council for Reviewing Books and Text in the Developing the Culture of Critique of Texts and Books of the Humanities Based on Upstream Documents of the Council - Hossein Moghiseh; Esmail Kavoosi; Abdalrahim Rahimi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of the present study was to evaluate the performance of the Council for Reviewing Books and Text in the Developing the Culture of critique of texts and books of the humanities, based on upstream documents of the council. Therefore, the combination method was used. The statistical population included all experts and reviewed books in council as well as other institutions and publications in the 1390s. The samples of the study were: I) Almost all articles and critiques, II) 24 experts and practitioners, and III) 10 interviews published in the book of the Re-Reading Council that were selected by purposeful sampling method. A checklist and a questionnaire were used to collect the data. The data were analyzed by chi-square and binomial tests, and qualitative content analysis. The research findings indicated that the council had received an acceptable grade in five criteria of six criteria and had a positive performance. Of course, there were some shortcomings in each of these criteria. Thus, some suggestions were made to improve and enhance the status of the council. It is recommended to redefine the scope of its members and take advantage of the advancements in information and communication technologies to disseminate and inform about the activities of the council.